PkM. PENDAMPINGAN ANAK MELENIAL DALAM MELESTARIKAN SENI DRAMATARI ARJA SEBAGAI WARISAN BUDAYA LELUHUR DI BANJAR TEGAL, DESA DARMA SABA, ABIANSEMAL BADUNG - I Ketut Muada; I Made Indra Sanjaya (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
A result of human ideals, tastes, and desires that produce works of art, bringing socio-cultural influences to Balinese society in particular. This influence needs to be filtered by developing Balinese cultures and studying the noble values ​​contained therein. In order to develop a national culture that has personality and national awareness, it is necessary to foster the ability of the community to preserve the art of arja drama by upholding noble social values. This description means that as the young generation of Bali, we must preserve regional culture, because regional culture is the root of national culture. One of the regional cultures that needs to be preserved is the performance of arja drama which is always adhiluhung. The art of arja drama has now developed into a complex art system and is full of educational values. The performance of arja drama in Bali harmoniously combines various types of art branches, including: dance, song, karawitan and literature. The plays always reflect cultural values ​​as the basic capital of Indonesian culture in general and Balinese culture in particular. The research problems are (1) strategies for mentoring millennial youth in preserving the Arja dance drama performance (2) The most appropriate story to learn and (3) community response regarding the preservation of Arja dance drama. This research is a descriptive-qualitative research formatted in a special study. The focus of this community service study is Mentoring Millennial Children in Preserving the Art of Arja Dance Drama Performance as an Ancestral Cultural Heritage in Banjar Tegal, Daramasaba Village, Abiansemal District, Badung Regency, Bali. The data were analyzed using a descriptive-qualitative method with steps as stated by Lacey and Luff (2001) in Patilima (2005:91), which include: data transcription, data identification and reduction, data classification, data description and interpretation, data triangulation, presentation of final results of the PKM.